Coronary microvascular health in patients with prior COVID-19 infection and no known CAD. (3rd October 2022) - Ahmed, A I; Saad, J M; Han, Y; Alahdab, F; Malahfji, M; Nabi, F; Mahmarian, J; Cooke, J P; Zoghbi, W A; Al-Mallah, M H
Abstract: Introduction: Although most patients recovering from acute COVID-19 infection have complete resolution of symptoms, some have cardiopulmonary symptoms lingering long after the acute phase of the disease. One proposed mechanism involves chronicity of COVID-19 associated with myocarditis and endotheliopathy. Purpose: To determine the coronary microvascular health of patients with prior COVID-19 and no known coronary artery disease (CAD) using positron emission tomography (PET). Methods: Cases consisting of patients without known CAD but previous COVID-19 infection who had clinically indicated PET imaging were matched 1:4 on clinical and cardiovascular risk factors to controls having no prior COVID-19 infection. Myocardial blood flow (MBF) in ml/gm/min was obtained from dynamic images at rest and peak hyperemia. The coronary flow reserve (CFR) was calculated as the ratio of stress to rest MBF of the left ventricle. Coronary microvascular dysfunction (CMD) was defined as CFR<2. Results: The study population consisted of 315 patients, 25% (n=80) of which had prior COVID-19 infection (mean±SD age 64±11 years, 46% men). The median (IQR) number of days between COVID-19 infection and PET imaging was 190 (85–268) days. After adjusting for age, gender and cardiovascular risk factors, patients with prior COVID-19 and no known CAD had a statistically significant higher odds of having a CFR <2 (OR 4.9, 95% CI 2.3–10.1 p<0.001) and CFR <2 normalized to patient's rate-systolic blood pressure product (OR 2.8, 95% CI 1.6–5.0 p=0.001). The annualized event rate for the composite outcome of all-cause death, myocardial infarction, admission for heart failure exacerbation and late revascularization was higher in cases vs controls and in those with CMD. Conclusion: Our analysis showed that patients with prior COVID-19 and no known CAD had higher rates of CMD, and that the presence of CMD was associated with higher risk of incident cardiovascular events. Funding Acknowledgement: Type of funding sources: None.